SLC5A3 depletion promotes apoptosis by inducing mitochondrial dysfunction and mitophagy in gemcitabine-resistant pancreatic cancer cells - Minsoo Kim; Woosol Chris Hong; Hyeon Woong Kang; Ju Hyun Kim; Dongyong Lee; Jae-Ho Cheong; Hye-Sol Jung; Wooil Kwon; Jin-Young Jang; Hyo Jung Kim; Joon Seong Park (Cell Death and Disease)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer with poor prognosis, largely due to the rapid development of chemoresistance in patients. Mitochondrial dynamics play a crucial role in cancer cell survival. Currently, the specific mechanisms underlying gemcitabine resistance in PDAC remain unknown. In this study, we identified the sodium/myo-inositol co-transporter solute carrier family 5 member 3 (SLC5A3) as a key modulator promoting chemoresistance in PDAC. SLC5A3 levels were significantly upregulated in gemcitabine-resistant PDAC cells, enhancing their cell survival by stabilizing the mitochondrial functions and inhibiting apoptosis. Mitochondrial analysis showed that SLC5A3 inhibition disrupted the mitochondrial dynamics, leading to increased reactive oxygen species production, mitochondrial fission, and impaired oxidative phosphorylation. Moreover, SLC5A3 inhibition activated the PTEN-induced kinase 1/Parkin-mediated mitophagy pathway, resulting in the excessive removal of damaged and healthy mitochondria, thereby depleting the mitochondrial reserves and sensitizing the cells to apoptosis. In vivo studies revealed that targeting SLC5A3 enhanced the efficacy of gemcitabine and significantly reduced the tumor growth. Collectively, these results suggest SLC5A3-mediated mitochondrial regulation as a promising therapeutic strategy to overcome gemcitabine resistance in PDAC.